MENGHADAPI ERA SOCIETY 5.0 DENGAN KELUARGA SAKINAH TELAAH SURAH AR-RUM:21 - Triska Candra Sari (Wahana Islamika: Jurnal Studi Keislaman, 2023)
Marriage aims to form a harmonious family as every married couple dreams of. Harmony requires cooperation between husband and wife in running the household. Family harmony will also change over time. As is the case in the era of society 5.0 that we will face where there is a development in information technology that is part of humans. In the family, there is often indirect communication, this is a challenge to create a sakinah family. Husband and wife must have a strong sense of self in dealing with problems, because the truth is that problems always exist in life, including the Prophet's family. This research was conducted with a qualitative approach. The type of research is library research, by collecting sources from journals, books or the web as references. This study has the conclusion that the sakinah family in the letter Ar-Rum: 21 according to the interpretation of some scholars explains that sakinah is obtained by marriage and offspring besides fulfilling other needs such as economy, education, and welfare. Sakinah families in the era of society 5.0 can also be pursued by maintaining communication with each other, getting to know each other's family characters, understanding each other, looking after each other.